2019
DOI: 10.1002/asia.201900501
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic C−H Borylation Using Iron Complexes Bearing 4,5,6,7‐Tetrahydroisoindol‐2‐ide‐Based PNP‐Type Pincer Ligand

Abstract: Catalytic C−H borylation has been reported using newly designed iron complexes bearing a 4,5,6,7‐tetrahydroisoindol‐2‐ide‐based PNP pincer ligand. The reaction tolerated various five‐membered heteroarenes, such as pyrrole derivatives, as well as six‐membered aromatic compounds, such as toluene. Successful examples of the iron‐catalyzed sp3 C−H borylation of anisole derivatives were also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…However, they have been scarcely used for stabilizing C−H borylation catalysts. Three classes of pincers have received attention: neutral 6 e − donors, monoanionic 5 e − donors, and dianionic 4 e − donors . The first type has been employed by the groups of Chirik, Cui, and Kamitani.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they have been scarcely used for stabilizing C−H borylation catalysts. Three classes of pincers have received attention: neutral 6 e − donors, monoanionic 5 e − donors, and dianionic 4 e − donors . The first type has been employed by the groups of Chirik, Cui, and Kamitani.…”
Section: Introductionmentioning
confidence: 99%
“…Cui has synthesized a cobalt(II) compound stabilized by a silylene‐pyridine‐silylene pincer, which enables reactions of pyridines, furans, and fluorinated arenes, whereas Kamitani has achieved efficient C−H borylation of arenes and heteroarenes using an iron complex bearing a quinoline‐based PNN ligand. Pincers donating 5 e − and 4 e − have been mainly used to stabilize iridium catalysts, in addition to some examples of iron, rhodium, and platinum . Chianese's group has observed that, in combination with NaO t Bu, iridium(III) complexes containing CCC‐pincer N ‐heterocyclic carbene ligands form active species for C−H borylation of disubstituted substrates.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the highest reported meta selectivity observed for the stoichiometric or catalytic C-H borylation of toluene. 23 This reaction is likely to proceed by a similar mechanism reported for [Ir(Bpin) 3 (L) 2 ] complexes (where L is a bisphosphine, bipyridine or phenanthroline ligand) which undergo s-CAM activation of the arene C-H bond. 24 This is the rst example of a high oxidation-state rhenium complex mediating C-H borylation, contrasting with previous examples that exploit complexes of lower oxidation-states.…”
Section: Stoichiometric Reactivity Ofmentioning
confidence: 68%
“…The iron derivative Pyr ( tBu PNP)Fe(N 2 ) 39‐Fe and the iron(II) hydride Pyr ( t BuPNP)Fe(H) 40 were both found to effectively catalyze the hydroboration of alkenes and alkynes with HBpin (see Scheme ) . Using catalytic amounts of the dimeric P i Pr 2 ‐substituted 4,5,6,7‐tetrahydroisoindol‐2‐ide‐hydridoiron(II) pincer complex 41 , catalytic C–H borylations of furans were also achieved (Scheme ) . For the C–H borylation of less activated arenes, B 2 Pin 2 has been used as a B‐transfer reagent, but these transformations are best carried out using the more reactive iron(II) methyl complexes Pyr ( R PNP)Fe(Me) as catalysts …”
Section: Pnp Pincers and Their Reactivity Patternsmentioning
confidence: 99%
“…Using catalytic amounts of the dimeric P i Pr 2 ‐substituted 4,5,6,7‐tetrahydroisoindol‐2‐ide‐hydridoiron(II) pincer complex 41 , catalytic C–H borylations of furans were also achieved (Scheme ) . For the C–H borylation of less activated arenes, B 2 Pin 2 has been used as a B‐transfer reagent, but these transformations are best carried out using the more reactive iron(II) methyl complexes Pyr ( R PNP)Fe(Me) as catalysts …”
Section: Pnp Pincers and Their Reactivity Patternsmentioning
confidence: 99%